How many medals will Great Britain win in the 2012 Olympics? - Stefani, R. (Significance, 2012)
Following methods used to estimate home advantage in team sports, Ray Stefani examines past Olympic home nation medal counts to estimate the home nation advantage and predict the number of medals to be won by Great Britain in the Summer Olympics in London, 2012.